Plant Evolution and the Origin of Crop Species (3rd Edition) - Hancock, James F (CABI, 2014)
It has been almost 20 years since the first edition of this book was published, and the amount of information available on plant evolution and crop origins has skyrocketed, particularly in the molecular arena. Where the molecular technologies have had the greatest impact is in tracing crop origins - determining parental species, finding out where crops were domesticated and identifying the genes that made the domestications possible. Molecular studies have also played a key role in testing long-standing evolutionary theories. Most of the hypotheses of Anderson, Grant, Heiser and Stebbins have proven robust, even as experimental technologies have dramatically shifted from morphological and cytogenetic compari- sons to gene chips and genome sequencing. Hypotheses concerning hybrid speciation, polyploidy and the role of chromosome rearrangements have been tested, retested and expanded as each new technology has emerged. The molecular studies have generated some surprises, such as the amount of chromosome repatterning and gene expression alterations associated with interspecific hybridiza- tion, and the high level of gene duplication found in all sequenced genomes, but in general each new molecular technology has supported the evolutionary hypothesis formulated decades ago. In this book I have tried to use, whenever possible, the historical evidence of evolutionary phenomena and crop origins. This may give the book an "old fashioned" feel, but I think that the information is still relevant and should not be lost in a cloud of new technologies. I have chosen to work from the past up to the present, rather than the reverse. It is likely that the growing wealth of molecular information will necessitate an alternative approach in any future editions, but so far I think that I can hold my ground.